Tat-Biliverdin Reductase A Exerts a Protective Role in Oxidative Stress-Induced Hippocampal Neuronal Cell Damage by Regulating the Apoptosis and MAPK Signaling - Sang Jin Kim (International Journal of Molecular Sciences, 2020)
Reactive oxygen species (ROS) is major risk factor in neuronal diseases including ischemia. Although biliverdin reductase A (BLVRA) plays a pivotal role in cell survival via its antioxidant function, its role in hippocampal neuronal (HT-22) cells and animal ischemic injury is not clearly understood yet. In this study, the effects of transducible fusion protein Tat-BLVRA on H2O2-induced HT-22 cell death and in an animal ischemia model were investigated. Transduced Tat-BLVRA markedly inhibited cell death, DNA fragmentation, and generation of ROS. Transduced Tat-BLVRA inhibited the apoptosis and mitogen activated protein kinase (MAPK) signaling pathway and it passed through the blood-brain barrier (BBB) and significantly prevented hippocampal cell death in an ischemic model. These results suggest that Tat-BLVRA provides a possibility as a therapeutic molecule for ischemia.